Facundity of Whipfin Silver Biddy Gerres filamentosus (Cuvier) from Sharavati Estuary, Central West Coast of India - and Bhat U. G2, Renuka G1*, (Recent Research in Science and Technology, 2011)
Fecundity of Gerres filamentosus varied from 48,300to 1,16760 in fishes ranging in size from 154 to 240 mm..Fecundity increases at the rate of cube of the total length .The number of ova per gram of body weight varied from 485 to 955, while the number of ova per gram ovary weight ranged from 11761 toÃ‚Â  24250. The relationship between weight of ovary and fecundity is linear and number of ova increases at a rate less than that in relation to total length and body weight.